A Rare Case of Breast Tuberculosis - Report and Literature Review - Banu, A; Poornima, R (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2011)
Isolated Tuberculosis of Breast is uncommon, even in developing countries where pulmonary and other extrapulmonary manifestations are endemic. The significance of Breast tuberculosis is due to rare occurrence and mistaken identity with breast cancer and pyogenic breast abscess. Breast Tuberculosis has no defined clinical features. Radiological imaging is not diagnostic. The main sign and symptoms of this patient included a painful tender lump in the breast. The diagnosis was confirmed by Fine Needle Aspiration Cytology. Anti Tubercular Treatment was the therapeutic main stay. Surgical intervention was reserved for aspiration of cold abscess and excision of residual sinuses and masses. DOI: 10.3126/saarctb.v7i2.4403 SAARC J. TUBER. LUNG DIS. HIV/AIDS 2010 VII(2) 30-33